QUR’ANIC INTERPRETATION AND MODERNITY: UNDERSTANDING THE ROLE OF TAFSIR IN CONTEMPORARY ISLAMIC THOUGHT - Umar Zakka; Taufik Setyaudin; Roswati Nurdin; Lady Eka Rahmawati (Journal of Noesantara Islamic Studies, 2026)
This study explores the evolving role of Qur’anic interpretation (tafsir) within the context of modernity and its significance for contemporary Islamic thought. Modern intellectual, social, and ethical transformations have generated new questions regarding the authority, methodology, and relevance of classical exegetical traditions, making tafsir a crucial site of engagement between revelation and changing realities. The objective of this research is to examine how tafsir functions as an intellectual mediator that enables Islamic thought to respond to modern epistemological and societal challenges while maintaining continuity with the Qur’anic tradition. The study employs a qualitative research design based on textual and interpretive analysis of selected classical and contemporary tafsir works that explicitly engage with modern issues. Hermeneutical and conceptual frameworks are used to analyze interpretive patterns, methodological orientations, and thematic emphases. The findings reveal that contemporary tafsir demonstrates significant methodological diversity, with a growing emphasis on contextualization, ethical reasoning, and thematic interpretation. The study concludes that tafsir plays a central role in negotiating the relationship between Islam and modernity, serving as a bridge between sacred text and contemporary thought.